2022
DOI: 10.2147/nss.s370334
|View full text |Cite
|
Sign up to set email alerts
|

Overweight/Obese Status Synergistically Worsens Nocturnal Time-to-Time Blood Pressure in Children with Obstructive Sleep Apnea

Abstract: Objective To investigate the influence of obstructive sleep apnea (OSA) severity and weight on blood pressure (BP) during nighttime sleep in children. Methods Habitually snoring children who were 3–14 years old and from Beijing Children’s Hospital between 1 January 2018 and 31 December 2020 were recruited. All participants completed polysomnography (PSG) and BP monitoring during different sleep stages using pulse transit time analysis. Subjects were divided into three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Logistic regression analysis revealed that children with obesity and moderate to severe OSA had a three‐fold increased risk of unfavorable BP 66 . Similar results were obtained by Wu et al 67 with overweight/obese children having higher BP in association with OSA. Another study by Chuang et al 68 investigated the associations of intermittent hypoxemia (IH), AHI, and weight status with hypertension in pediatric OSA.…”
Section: Outcomes Of Sdbsupporting
confidence: 83%
“…Logistic regression analysis revealed that children with obesity and moderate to severe OSA had a three‐fold increased risk of unfavorable BP 66 . Similar results were obtained by Wu et al 67 with overweight/obese children having higher BP in association with OSA. Another study by Chuang et al 68 investigated the associations of intermittent hypoxemia (IH), AHI, and weight status with hypertension in pediatric OSA.…”
Section: Outcomes Of Sdbsupporting
confidence: 83%
“…In addition to directly and indirectly causing non-dipping status, overweight/obese status could enhance the unfavorable impact of certain conditions on nocturnal BP fall. A recent study found that the influence of OSAS on pediatric BP was dependent on weight and being overweight/obese could synergistically worsen nocturnal BP in children with OSAS [ 34 ].…”
Section: Discussionmentioning
confidence: 99%